Impact of bisphenol a on the levels of vascular calcification biomarkers in type 2 diabetes mellitus with vascular complications: A case-control study - Mohanraj Nehru; Prasanth Subramaniam; M.S. Jancy; Prabhu Durairaj; J.S. Kumar; Venkataraman Prabhu (Emerging Contaminants)
Bisphenol A (BPA) is an endocrine disruptor present in polycarbonate plastics used in food containers and water bottles that resists insulin action and leads to type 2 diabetes mellitus (T2DM). However, there is scant research on the impact of BPA on T2DM-related vascular complications. Fetuin-A (FTA) and osteoprotegerin (OPG) are crucial markers for vascular calcification, which is the primary risk factor for developing vascular complications. This study aims to link external factor BPA levels with the vascular calcification markers FTA and OPG in diabetic subjects with and without vascular complications. Therefore, 120 study subjects were included and divided as control (n = 30), T2DM with cardiovascular diseases (CVD) (n = 30), T2DM with diabetic nephropathy (DN) (n = 30), and T2DM without vascular complications (n = 30). Serum and urinary FTA, OPG, and BPA levels were measured using an ELISA. FTA (AHSG) and OPG (TNFRSF11B) gene expression were analyzed using qPCR. Both serum (p < 0.001) and urinary BPA (p < 0.001) were found higher in T2DM with CVD and DN than T2DM without vascular complications and control. Also, T2DM with CVD and DN patients had lower serum and urinary FTA protein levels and increased serum and urinary OPG (p < 0.001) levels than T2DM without vascular complications and control. Moreover, FTA (AHSG) gene expression was negatively associated with serum BPA (p < 0.001) and urinary BPA (p < 0.01). Likewise, OPG (TNFRSF11B) gene expression was positively significant with serum BPA (p < 0.001) and urinary BPA (p < 0.01) in the study groups. These findings suggest that elevated blood and urinary BPA levels contribute to the severity of vascular complications in T2DM patients through vascular calcification.